Simulation of Lighting Comfort at Auditorium Hall 1, Shared Facility Pagoh - ISHAK, MUHAMMAD HAKIMI BIN ISHAK; Mohd Fahmi Bin Abdul Rahman, (Progress in Engineering Application and Technology, 2025)
Lighting level is one of main important aspect of a building, it is a system that function all activities inside the building. Lighting should make the appearance of learning looks better and the occupants feel more comfortable since light has a very carrying ability to dictate productivity and moods of the inhabitants. Inadequate amount of lighting can be glare and in essence makes the eyes physically uncomfortable or leads to reduced visual clarity. This study was to assess whether the lighting level in auditorium hall 1 meet the standard requirements and analysed the effect of lighting on visual comfort and perception in auditorium hall 1. Methods used in this study were field measurements, questionnaire surveys and simulations using the Dialux software. The field measurement method was using a lux meter to identify the lighting level that must be in accordance with the standard. The findings of this study showed that the lighting level is range 181 – 243 lux below than 300-500 lux did not meet the Malaysian standard (MS 1525). However, simulation method used the Dialux software, while the 105-respondent are participated in questionnaire survey and analysis used quantitative descriptive statistics for frequency, mean, and standard deviation the descriptive analysis showed that the mean scores for perception (2.0), comfort (1.9) and acceptability (1.83) ranged from 1.81 to 2.60, indicating low satisfaction among auditorium users regarding visual comfort. In conclusion, the lighting recommendation is optimizing the positioning of lighting fixtures within the auditorium. Upgrade the existing light fixtures with the latest energy efficient LED systems.